2017
DOI: 10.1108/ijse-03-2016-0086
|View full text |Cite
|
Sign up to set email alerts
|

The threshold effects of household indebtedness on multidimensional poverty

Abstract: DeclarationBy submitting this dissertation electronically, I declare that the entirety of the work contained therein is my own, original work, that I am the sole author thereof (save to the extent explicitly otherwise stated), that reproduction and publication thereof by Stellenbosch University will not infringe any third party rights and that I have not previously in its entirety or in part submitted it for obtaining any qualification.This dissertation includes two published and one accepted but not yet publi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 172 publications
1
6
0
1
Order By: Relevance
“…The mean values of the government subsidy funds for housing construction among PRPHs and PUPHs (4333.33 and 4111.11 CNY) were lower than those of the sample (8196.28 CNY). The mean values of the debt for housing construction among PRPHs and PUPHs (5750 and 12000 CNY) were higher than the mean level of the data (3803.27 CNY), and Ntsalaze et al [28] also stated that high household indebtedness was a severe social scourge. All of the PUPHs did not have complete medical insurance, possibly out of cost concerns [33].…”
Section: Anticipated Determinants Of Prphs and Puphsmentioning
confidence: 67%
See 1 more Smart Citation
“…The mean values of the government subsidy funds for housing construction among PRPHs and PUPHs (4333.33 and 4111.11 CNY) were lower than those of the sample (8196.28 CNY). The mean values of the debt for housing construction among PRPHs and PUPHs (5750 and 12000 CNY) were higher than the mean level of the data (3803.27 CNY), and Ntsalaze et al [28] also stated that high household indebtedness was a severe social scourge. All of the PUPHs did not have complete medical insurance, possibly out of cost concerns [33].…”
Section: Anticipated Determinants Of Prphs and Puphsmentioning
confidence: 67%
“…To predict poverty of household level, Puurbalanta [21] introduced the age of householder, the educational years of householder, and the number of family members. Ntsalaze et al [28] indicated that the educational years of householder were associated with multidimensional poverty, where they also introduced the age of householder, the number of the juveniles under 16, and the number of family members to predict the household's deprivation score. Rupasingha et al [29] indicated that less the quantity of workforce might exacerbate poverty.…”
Section: Data and Methodology A Datamentioning
confidence: 99%
“…Because the finding in literature is skewed toward the negative effect of household debt on consumption and growth (Alter et al, 2018;Mian et al, 2017;Dynan & Edelberg, 2013) and debt as a predictor and determinant of financial crisis (Alter et al, 2018;Schularick & Taylor 2012;Jorda, Schulauck, & Taylor, 2013, 2016Mian & Sufi, 2010), research dynamism in this area is aimed to find the optimal level of household debt. However, to date, few studies examine this issue (Lombardi, Mohanty, & Shim, 2017;Ntsalaze & Ikhide, 2017), leaving room for a different dimension of study to be conducted. By means of a simple dummy that sets a certain threshold level, Lombardi et al, (2017) find that household debt at 60 percent and 80 percent (of GDP) lower consumption and growth respectively for a pool of countries, whereas Ntsalaze and Ikhide (2017) identify a tipping point of 42.5 percent of household debt to disposable income.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Program pembiayaan ini merupakan bagian dari kegiatan inklusi keuangan dari BPRS, dimana pelaksanaannya melalui koperasi syariah, yang dalam hal ini oleh Koperasi Karya Usaha Mandiri Syariah. Sebagai bagian dari kegiatan inklusi keuangan yang merupakan program nasional dari OJK (Otoritas Jasa Keuangan), maka seharusnya program ini juga disertai kegiatan literasi serta pembinaan ekonomi dan manajemen terhadap para pelaku UMi (Lungile & Sylvanus, 2017). Namun dalam prakteknya, BPRS melalui koperasi, belum banyak melakukan pembinaan terhadap UMi secara menyeluruh, terkait pengembangan kelembagaan.…”
Section: Faktor Pendukung Dan Penghambatunclassified